Umur Simpan Buah Salak Dengan Modifikasi Atmosfer Dalam Kemasan Plastik Polietilen - Samiha Syamsuddin (Balai Besar Kimia dan Kemasan, 1998)
Experiment on shelf life of salaca fruit using LDP E plastic has been established. The comparation of salaca fruit shelf life packed with LDP E plastics with and without MAP has been investigated during this experiment. The result show that salaca fruit packed with LDP E plastic with MAP has longer shelf life compare to the other one packed with LDP E plastic without MAP.The shelf life of salaca fruit packed with MAP can reach 3 2 days, mean while the other one packed without lv!AP can only reach 11 days.